Impact of COVID 19 Infection and Development of Cardiovascular Disease - Hongyang Shu; Zheng Wen; Na Li; Zixuan Zhang; Bala Musa Ceesay; Yizhong Peng; Ning Zhou; Dao Wen Wang (Advancement and New Understanding in Medical Science Vol. 9, 2024)
This review focuses on the effects of SARS-CoV-2 on the cardiovascular system. We reviewed the evidence and mechanisms of different cellular injuries in myocardial tissues and the clinical manifestations of cardiovascular involvement and discussed issues related to myocardial injury in the recovery stage and after vaccination. The emergence of coronavirus disease 2019 (COVID-19) has overwhelmed the medical systems of several countries and posed unprecedented challenges to the mankind. Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), quickly spread worldwide and led to over 581 million confirmed cases and over 6 million deaths as 1 August 2022. The binding of the viral surface spike protein to the human angiotensin- converting enzyme 2 (ACE2) receptor is the primary mechanism of SARS-CoV-2 infection. Not only highly expressed in the lung, ACE2 is also widely distributed in the heart, mainly in cardiomyocytes and pericytes. The strong association between COVID-19 and cardiovascular disease (CVD) has been demonstrated by increased clinical evidence. Preexisting CVD risk factors, including obesity, hypertension, and diabetes etc., increase susceptibility to COVID-19. In turn, COVID-19 exacerbates the progression of CVD, including myocardial damage, arrhythmia, acute myocarditis, heart failure, and thromboembolism. Moreover, cardiovascular risks post recovery and the vaccination-associated cardiovascular problems have become increasingly evident. To demonstrate the association between COVID-19 and CVD, this review detailly illustrated the impact of COVID-19 on different cells (cardiomyocytes, pericytes, endothelial cells, and fibroblasts) in myocardial tissue and provides an overview of the clinical manifestations of cardiovascular involvements in the pandemic. Finally, the issues related to myocardial injury post recovery, as well as vaccination-induced CVD, has also been emphasized. Vaccine development and ongoing research on SARS-CoV-2 reflects the tireless efforts of the scientific community, healthcare workers, and government agencies. The lessons learned from our response to COVID-19 will hopefully prepare us for future pandemics.